Multi-Objective optimization in computational intelligence theory and practice - Bui; Alam (Premier reference source, 2008)
"This book explores the theoretical, as well as empirical, performance of MOs on a wide range of optimization issues including combinatorial, real-valued, dynamic, and noisy problems. It provides scholars, academics, and practitioners with a fundamental, comprehensive collection of research on multi-objective optimization techniques, applications, and practices"--Provided by publisher.